Antibacterial activity of essential oil of foeniculum vulgare miller against multiresistant gram-negative bacilli from nosocomial infections - Araque, María; Rojas, Luis; Usubillaga, Alfredo (Ciencia)
The essential oil of Foeniculum vulgare Miller was analized by GC and GC/MS. Fourteen components, representing the 99.98% of the oil, were identified; trans-anethole (64.08%), a-phellandrene (14.54%), and a-pinene (9.38%) were the most abundant constituents. Antimicrobial tests were carried out against 30 strains of multiresistant Gram-negative bacilli isolated from patients with nosocomial infections. Results show that the oil exhibited a strong inhibitory activity against all strains of the Gram-negative bacilli tested, regardless of bacterial species, type or number of resistance markers. These findings suggest that the essential oil of aerial parts of Foeniculum vulgare Miller have inhibitory activity against multiresistant Gram-negative bacilli from patients with nosocomial infections. Thus, the investigated essential oil has potential antibacterial activity, which can be further exploited to develop new drugs to treat infections produced by important multiresistant Gram-negative human pathogens.